Crystallinity Engineering of Hematite Nanorods for High‐Efficiency Photoelectrochemical Water Splitting - Wang, Degao (Adv Sci (Weinh), 2015)
An effective strategy to overcome the morphology evolution of hematite nanorods under high‐temperature activation is presented, via tuning the crystallinity and sintering temperature by substrate modification. It is demonstrated that the as‐prepared doping‐free hematite nanorods with fine nanostructures obtain a significantly higher photocurrent density of 2.12 mA cm(−2) at 1.23 V versus RHE, due to effective charge separation and transfer. [Image: see text]